Indonesian EFL Students’ Learning Styles - Nostalgianti Citra Prystiananta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This research aims at investigating students’ learning styles of Accounting Program of AAK PGRI Jember in learning English as Foreign Language. EFL students have their own ways in learning English which they think as the most enjoyable way to a better comprehension of the material. By investigating their learning styles in learning English, teachers may know the best ways to treat their students to reach a better improvement. In this research, the sample was 41 students from three different academic years who were learning EFL. The data were collected through questionnaire and interview. The questionnaire contained 30 items of statements about 6 learning styles according to questionnaire by Reid (1987). An open-ended interview was conducted to support quantitative data gained from questionnaires. The result presents that students of Accounting Program of AAK PGRI Jember most preferred Visual style (44%) as their style in learning English. And Individual style (4%) as the least preferred style. It can be concluded that students of Accounting Program of AAK PGRI Jember enjoy learning English best by the assistance of pictures, charts, and videos because they can comprehend the material better. They also did not enjoy to learn individually because they were not independent type of student who enjoy being alone. Keywords: TEFL, language learning styles